A clinical study of mastoid ventilation tube in tympanoplasty - Harish Swamy Dharmagadda; Kathyayani Burugula; Parasa, Sujay Kumar (Asian Journal of Medical Sciences, 2023)
Background: A ventilated middle ear space is an essential component of a functioning middle ear transformer mechanism. A mastoid ventilation tube (MVT) placed post-aurally in the antrum near the aditus is used in this study for the benefit of improvement in results of tympanoplasty. In support of this concept, very few experimental documents are reported. Aims and Objectives: The aims of this study were to find out if the MVT has any effect on the outcome of tympanoplasty in cases of chronic suppurative otitis media (CSOM) tubo-tympanic disease. Materials and Methods: This study was performed in 50 cases which were selected from the total number of cases using stratified random sampling method. In the research, patients with CSOM, who did not respond to medical therapy and required a combined approach tympanoplasty, were enrolled. Patients who needed just myringoplasty and those found to have cholesteatoma intraoperatively were not included in the research. Results: The study showed significant improvement in graft uptake, air-bone closure, and hearing in cases with MVT, thus resulting in better success rate in cases with MVT than cases without MVT. Furthermore, most of the cases had sclerosed mastoids and very few cases had complications such as MVT block and post-operative discharge. Conclusion: The MVT had a beneficial effect on the final outcome of combined approach tympanoplasty in cases of CSOM tubo-tympanic type active stage.